The influence of active knowledge sharing strategies on fifth-grade students’ social studies learning outcomes - Amanda, Rifani; Abdullah, Kusmajid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This study aims to determine the effect of using active knowledge- sharing learning strategies. The research location is one of the elementary schools in Bekasi, to be precise at the fifth-grade level during semester 2 of the 2021/2022 academic year, especially in social studies subjects. While the research method used is a quantitative research method with a Quasi-Experimental Design research design. The type of sample used was Saturated Sampling with a total of 70 participants divide into 2 class which is 35 at experimental class and 35 in a control class, with 30 questions given to participants. From the results of the calculation of the t test in the study, it obtained a value of t count = 5.8970 ≥ t table 1.999 which stated that there was a significant effect of learning using the Active Knowledge Sharing learning strategy on social subject learning outcomes in one of the elementary schools in Bekasi. The Active Knowledge Sharing learning strategy applied by teaching staff to their students can increase the level of creativity and courage of a student so that students can learn effectively and have fun, especially in this study the subjects taken were social subjects.